IMPLEMENTASI CORPORATE GOVERNANCE PADA CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Endiana, I Dewa Made (Jurnal Riset Akuntansi (JUARA), 2019)
Company value is a perception of investors on the level of success of the company that isoften associated with stock prices. High stock prices make the value of the company also high.A high corporate value will make the market believe not only in the company’s current performancebut also in the company’s prospects in the future. This study aims to determine the effectof corporate social responsibility on corporate value with Corporate Governance as a moderatingvariable in LQ 45 companies.This research was conducted at LQ 45 companies listed on the Indonesia Stock Exchange(IDX). The number of samples taken was 36 companies with purposive sampling method. Theresearch period from 2016 to 2017. The data analysis technique used is PLS ModerationThe results of this study indicate that corporate social responsibility (CSR) has a positiveeffect on firm value. Corporate Governance is not able to moderate the influence of corporatesocial responsibility (CSR) on corporate value.